Spiritual Tourism in India: Narratives of pilgrims (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
India has become one of the prominent  destinations for spiritual tourism with several  international tourists visiting multiple spiritual  tourist sites for their spiritual or religious  fulfilment. Limited research exists that investigate  in depth what really motivates an individual  to take on a spiritual journey. Literature also  demands enrichment in terms of challenges or  barriers to a spiritual tourism. Feedback from  the pilgrims can help shrine administration to  effectively utilise the donor money in improving  the facilities during the journey and experience  of the spiritual tourist. Through this paper, we  make an effort to address this gap by conducting  in-depth interviews of pilgrims of two most  prominent spiritual tourism sites in North India,  analysing their narratives using interpretative  methods. We present pilgrim’s feedback on the  motivational aspects of their spiritual tourism  as well as challenges encountered during the  journey. Feedback from them is reported for  enhanced experience.
Keywords: Spiritual Tourism; India; Narratives; Pilgrims; Experience